2023
DOI: 10.14800/iogr.1219
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Miscibility Pressure Prediction Method Based On PSO-GBDT Model

Abstract: With the development of EOR technology, CO2 flooding was a very promising method to improve the recovery of conventional and unconventional oil reservoirs. MMP (minimum miscibility pressure ) was one of the important parameters of the CO2 flooding, and the use of an artificial intelligence algorithm can accurately predict the MMP, which was important to evaluate the effect of CO2 flooding development in the reservoir.This work presents methods to automatically find optimal parameter settings for machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The authors utilized 201 data points, and the reliability of their network was deemed consistent. He et al suggested five fitting approaches, among which the evolved gradient-boosting decision tree with particle swarm optimization (PSO-GBDT) proved to be the most accurate. It achieved accuracy values of 99% and 97.6% during the training and testing phases, respectively.…”
Section: Progress On Modeling the Mmp Of The Co2 – Oil Systems Using ...mentioning
confidence: 99%
“…The authors utilized 201 data points, and the reliability of their network was deemed consistent. He et al suggested five fitting approaches, among which the evolved gradient-boosting decision tree with particle swarm optimization (PSO-GBDT) proved to be the most accurate. It achieved accuracy values of 99% and 97.6% during the training and testing phases, respectively.…”
Section: Progress On Modeling the Mmp Of The Co2 – Oil Systems Using ...mentioning
confidence: 99%